Single-cell analysis of FOXP3 deficiencies in humans and mice unmasks intrinsic and extrinsic CD4(+) T cell perturbations - BARIŞ, SAFA (NATURE RESEARCH, 2021)
FOXP3 deficiency in mice and in patients with immune dysregulation polyendocrinopathy enteropathy X-linked (IPEX) syndrome results in fatal autoimmunity by altering regulatory T (T-reg) cells. CD4(+) T cells in patients with IPEX syndrome and Foxp3-deficient mice were analyzed by single-cell cytometry and RNA-sequencing, revealing heterogeneous T-reg-like cells, some very similar to normal T-reg cells, others more distant. Conventional T cells showed no widespread activation or helper T cell bias, but a monomorphic disease signature affected all CD4(+) T cells. This signature proved to be cell extrinsic since it was extinguished in mixed bone marrow chimeric mice and heterozygous mothers of patients with IPEX syndrome. Normal T-reg cells exerted dominant suppression, quenching the disease signature and revealing in mutant T-reg-like cells a small cluster of genes regulated cell-intrinsically by FOXP3, including key homeostatic regulators. We propose a two-step pathogenesis model: cell-intrinsic downregulation of core FOXP3-dependent genes destabilizes T-reg cells, de-repressing systemic mediators that imprint the disease signature on all T cells, furthering T-reg cell dysfunction. Accordingly, interleukin-2 treatment improved the T-reg-like compartment and survival. FOXP3 deficiency leads to dramatic loss of immune homeostasis. This multicenter collaborative group finds that loss of FOXP3 function only disrupts a few core genes, but this unmasks a degree of systemic inflammation, and it is this environment that then strongly perturbs T-reg cells.